Pengaruh Metode Ekstraksi terhadap Kadar Fenol dan Flavonoid Total, Aktivitas Antioksidan serta Antilipase Daun Jati Belanda (Guazuma ulmifolia) - Nuri, Nuri; Puspitasari, Endah; Hidayat, Mochammad Amrun; Ningsih, Indah Yulia; Triatmoko, Bawon; Dianasari, Dewi (Fakultas Farmasi Universitas Andalas, 2020)
The leaf of Guazuma ulmifolia has been used traditionally for antiobesity. The activity of antiobesity was affected by the content of bioactive compounds. Extraction is the primary step to obtain bioactive compounds from plant material. The method and solvent used for extraction are crucial factors to produce extracts that have a high amount of active compounds. This study aims to determine the total phenolic and total flavonoids content from ethanolic extracts, water extract, and infusions of G. ulmifolia leaf and to evaluate the antioxidant and antilipase activity. Folin-Ciocalteu method was used to determine the phenolic content, while flavonoid content determination was done using aluminium chloride colorimetric assay. The antioxidant activity was done using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, and the antilipase activity was quantified using p-nitrophenol release from p-nitrophenyl butyrate (p-NPB) substrate-colorimetric assay. The result of G. ulmifolia leaf extraction showed that the highest yield was obtained from water extraction (10.50%). Whereas, the ethanolic extract was showed the highest total phenolic content (67.761±1.811 mg GAE/g extract) and the highest total flavonoid content (124.643 ± 1.033 mg QE/g extract). The same extract also exhibited the highest antioxidant activity (IC50 = 6.544 ± 0.271 µg/mL) and antilipase activity (IC50 = 307.280 ± 21.430 µg/mL).